EMBRACING SPIRITUALITY IN THE WORK OF FRONTLINE NURSING HOME STAFF. (20th December 2022) - Lopez, Ruth Palan; Hendricksen, Meghan; Roach, Ashley; Rogers, Anita Hendrix; Mitchell, Susan
Abstract: Good end-of-life care for nursing home (NH) residents and their families provides for spiritual support, however, the role that spirituality plays in the work of NH staff has not been well described. To understand more about spirituality and NH staff, we examined interview data generated from the Assessment of Disparities and Variation for Alzheimer Disease Nursing Home Care at End of Life (ADVANCE) study, a large qualitative study conducted in 14 NHs to examine differences in end-of-life care for residents with advanced dementia. We examined semi-structured interview data from nurses (Registered Nurses and Licensed Practical Nurses) (n=45) and certified nursing assistants (CNAs) (n=25) who described the role of spirituality or God in response to questions around their experience caring for residents with advanced dementia. Data were analyzed using the constant comparative method. Most participants were female (93%). Thirty-four identified as Black, 29 as white, and 7 as other racial groups. The average age was 47.8 years, and the average years of experience was 16.2 years. Participants reported several religious affiliations including Baptist (23); Agnostic/Atheist (2), Catholic (7), Methodist (4), Muslim (1), Other/Unaffiliated/Refused (18), Pentecostal (4), and Christian (9). We found that for many nurses and CNAs, God played an important role in their work including providing meaning and purpose, providing them with resilience to cope with frequently losing residents that they consider "family." The voices of the participants were powerful and provide important insights into potential strategies to retain and support these essential, front-line providers.